2013
DOI: 10.1111/maec.12063
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the sponge assemblage ofMediterranean coralligenous concretions along a millennial time span

Abstract: The Mediterranean coralligenous substratum is a hard bottom of biogenic origin, mainly composed of calcareous algae, growing in dim light conditions. Sponges are among of the most representative taxa of the coralligenous assemblages, with more than 300 recorded species of different habits: massive, erect, boring and insinuating. When sponges die, their siliceous spicules remain trapped in the biogenic concretion, offering the opportunity to describe the coralligenous spongofauna over a very long span of time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Moreover, in the coralligenous habitat, the presence of pockets of soft-sediments allows the contemporary presence of both hard-and soft-bottom species (Ballesteros, 2006) and the peculiar structure leads to the entrapment of sediments that can represent a sort of black box, telling the story of the ancient assemblages (Bertolino et al, 2014). Scheffers et al (2010) demonstrated that in Curaçao reefs, cryptic suspension feeders, especially sponges, covered more than 60% of the inner cavity surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the coralligenous habitat, the presence of pockets of soft-sediments allows the contemporary presence of both hard-and soft-bottom species (Ballesteros, 2006) and the peculiar structure leads to the entrapment of sediments that can represent a sort of black box, telling the story of the ancient assemblages (Bertolino et al, 2014). Scheffers et al (2010) demonstrated that in Curaçao reefs, cryptic suspension feeders, especially sponges, covered more than 60% of the inner cavity surface.…”
Section: Resultsmentioning
confidence: 99%
“…Bertolino et al (2013), sectioning big coralligenous blocks into slices identified the presence of 27 exclusively endolithic species giving an idea of the richness of this group inside the coralligenous substrata. Moreover, it was stated that the diversity of coralligenous sponges has remained stable over a millennial span of time, and this extended stability may be related to the en- vironmental stability of the inner habitat of the conglomerates (Bertolino et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This lack of information has been reinforced by recent studies focusing on the diversity of Porifera (Bertolino et al . ; Calcinai et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…As highlighted by Ballesteros (2006), knowledge about the actual biodiversity hosted by this habitat has yet to be characterized. This lack of information has been reinforced by recent studies focusing on the diversity of Porifera (Bertolino et al 2014;Calcinai et al 2015). There is an increasing interest in the characterization of the distribution of this peculiar habitat (Martin et al 2014), but a shared monitoring approach has still not been developed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Probable high levels of chemical erosion are also shown by characteristic circular marks of dissolution (Fig. 9B) present on spicules (Bertolino et al, 2014).…”
Section: Endolithic Spongesmentioning
confidence: 98%